Identifikasi Penurunan Kinerja Cargo Oil Pump untuk Mendukung Kelancaran Proses Bongkar Muatan di MT. Pangrango - Angelina Adria S. P; Amad Narto; Moh.Sapta Heriyawan (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
The Cargo oil pump is one of the auxiliary units on board a ship, used to transfer cargo from one location to another during loading and unloading operations. On the MT Pangrango vessel, an issue occurred with the cargo oil pump: its performance declined, resulting in slow suction during the unloading process. This problem hindered efficient cargo operations, as the pump was not functioning properly.This study aims to identify the contributing factors, impacts, and countermeasures for the decreased performance of the cargo oil pump. The research methodology applied in this thesis involved a descriptive approach combined with Miles and Huberman’s analytical method, with data validity tested via triangulation. Data collection techniques used to identify the problem included observation, interviews, documentation, and literature review.The results revealed that the pump’s shaft was worn due to excessive friction, and the ball bearing s exhibited wear and disintegration caused by lack of lubrication (grease). The recommended corrective actions were to add material to the shaft , perform realignment to correct any shaft misalignment, and implement routine maintenance—specifically, monthly grease lubrication. These measures, when properly applied, can significantly reduce the risk of Cargo oil pump damage.